City-Maut in Stockholm - eine politökonomische Analyse. - Marner, Torsten (Deutscher Verkehrs-Verl., 2007)
Zehn Jahre nach dem Scheitern des so genannten "Dennis-Package" als erstem Versuch, Straßenbenutzungsgebühren in Schwedens Hauptstadt einzuführen, wurde den Stockholmer Bürgern am 17. September 2006 durch ein Referendum die Gelegenheit zur Entscheidung über die Einführung einer City-Maut in der Innenstadt gegeben. Dem Referendum gingen die Trials, ein City-Maut-Testlauf, voraus. Mehrheitlich stimmten die Wähler am Tag des Referendums für eine Fortsetzung der Maut und bildeten die Grundlage der Entscheidung für eine permanente Innenstadtmaut seit August 2007. difu

After the failed introduction of a road toll system ten years ago, 2007 witnessed - in the wake of a public referendum - the adoption of a system of road user charges, previously tested, for the centre of Stockholm. The report covers the factors closely associated with the new political economy, which have been applied to investigate the determinants responsible for the success or failure of Stockholm's road toll systems. It is absolutely essential for the government - as the political decision-maker - to secure the approval of, and enjoy the long-term acceptance by, the electorate notably so in view of a forthcoming general election. The report shows the measures aimed at gaining public support by way of an extensive campaign that highlights the use made of the income derived from toll charges and the resultant, often not-too-obvious, benefits. It would appear that short-term interests pursued by politicians do not work in favor of pushing for road tolls as has been confirmed by the failure of such a system in the nineties. difu
Keywords: Verkehr; Verkehrspolitik; Stadtverkehr; Innenstadt; Straßenverkehr; Gebühr; City-Maut; Straßenbenutzungsgebühr; Volksabstimmung